Physical stability test of moringa leaf extract (Moringa oleifera L.) in mouthwash preparation: Uji stabilitas fisik ekstrak daun kelor (Moringa oleifera L.) dalam sediaan obat kumur - Anggestia, Wulan; Anggraini, Netta; Nuha, Fathinah (Makassar Dental Journal PDGI Makassar, 2025)
Many mouthwashes in circulation today have the risk of side effects and also not a few synthetic ingredients that have a pungent aroma, so that other alternative mouthwashes made from herbs are needed. This study aims to evaluate the physical stability of moringa leaf extract (MLE) in mouthwash preparations based on pH, viscosity, stability, and organoleptic tests. With the design of post-test only control experimental research using sample of pre-clinical students class 2024 Faculty of Dentistry, Baiturrah-mah University. MLE was prepared using maceration method with 96% ethanol into mouthwash preparations of 0.01%, 0.02%, 0.04%; positive control was chlorhexidine 0.2%, and negative control was aquadest. The physical stability of the mouthwash was evaluated for colour, aroma, taste, and shape. MLE mouthwash 0.01%, 0.02%, and 0.04% had neutral pH values, with good stability test without separation, viscosity met the standard (≤7.25 cPs), organoleptic test was liked by more than 80% of res-pondents. It is concluded that MLE in mouthwash preparation has good physical stability and is most favoured by respondents with a concentration of 0.02%.